Addressing Bullying of Students with Autism: Suggestions for Families and Educators. (January 2015) - Hong, Ee Rea; Neely, Leslie; Lund, Emily M.
Bullying or any aggressive behavior of a more powerful person or group toward a less powerful person is a widespread problem in the U.S. educational system. While bullying is a significant problem for all students, students with an autism spectrum disorder (ASD) have a particularly high incidence rate of becoming victims of bullying. The social and communication deficits characteristic of students with ASD provide significant challenges in teaching and preparing these students for bullying situations. Cooperative work between teachers and parents, analyzing an individual student's needs, educating the student about bullying, teaching how to cope with and reporting it in both controlled settings and natural environments, and developing a monitoring system are key components of preventing the students with ASD from being bullied. An illustrative example and practical suggestions and approaches are provided.